איך אתה לפשט 12-15sqrt6 + 8sqrt6 - 10sqrt36?

איך אתה לפשט 12-15sqrt6 + 8sqrt6 - 10sqrt36?
Anonim

תשובה:

# 48-7sqrt (6) #

הסבר:

# 12-15sqrt (6) + 8sqrt (6) -10sqrt (36) #

# = 12-15sqrt (6) + 8sqrt (6) -10sqrt (6 ^ 2) #

# = 12-15sqrt (6) + 8sqrt (6) -10 * 6 #

# = 12-15sqrt (6) + 8sqrt (6) -60 #

# = 12-60 + (- 15 + 8) sqrt (6) #

# = - 48-7sqrt (6) #

תשובה:

# -48- (7 * sqrt (6)) #

הסבר:

(+) - 10 * sqrt (36)) # # + (- 15 * sqrt)

אנחנו יודעים את זה #sqrt (36) = 6 #.

לכן, # 12 + (- 15sqrt (6)) + (8 * sqrt (6)) + (- 60) #.

#12-60=-48#

לכן, # -48 + (- 15sqrt (6)) + (8 * sqrt (6)) #

עכשיו, להוציא #sqrt (6) # משני הסוגריים האחרונים.

זה ייתן לנו # -48 + (sqrt (6) * (- 15 + 8)) #

#-15+8=-7#

אז התשובה תהיה # -48- (7 * sqrt (6)) #